Alarums & excursions : improvising politics on the European stage - Middelaar, Luuk van, 1973- (Agenda Publishing, 2019)
Crisis after crisis has beset the European Union in recent years - Greek sovereign debt, Russian annexation of Crimea, unprecedented levels of migration, and the turmoil created by Brexit. An organization originally designed to regulate and enforce rules about fishing rights, wheat quotas and product standards has found itself on the global stage forced to grapple with problems of identity, sovereignty and solidarity without a script or prompt. From Paris to Berlin, London to Athens, European leaders have had to improvise on issues that the Union was never set up to handle and which threaten to engulf this unique political entity. And they have had to do so in full view of an increasingly disenchanted and dissonant public audience. In this candid and revealing portrayal of a Europe improvising its way through a politics of events and not rules, Luuk van Middelaar makes sense of the EU's political metamorphosis over its past ten years of crisis management. Forced into action by a tidal wave of emergencies, Van Middelaar shows how Europe has had to reinvent itself by casting off its legal straitjacket and confronting hard issues of power, territorial borders and public authority. Alarums and Excursions showcases the fascinating relationship between the Union and the European heads of government, and the stresses it must withstand in dealing with real world events. For anyone seeking to understand the inner power play and constitutional dynamics of this controversial, but no less remarkable, political institution, this book provides.-- Provided by publisher.
Keywords: European Union -- Foreign relations -- 20th century.; European Union -- Foreign relations -- 21st century.; European Union; Europäische Union; Crises -- European Union countries.; European Union countries -- Politics and government -- 21st century.; Crises (Sciences sociales) -- Pays de l'Union européenne.; LAW -- International.; POLITICAL SCIENCE / World / European; Crises; International relations; Politics and government; European Union countries; Europäische Integration; Krise; Politisches Handeln; Europese Unie.; Crises.; 1900-2099; Electronic books.